Mathematical Biology Models of Parkinson's Disease - Bakshi, Suruchi; Chelliah, Vijayalakshmi; Chen, Chao; Graaf, Piet H. (CPT: pharmacometrics and systems pharmacology, 2019)
Parkinsons disease (PD) is a progressive neurodegenerative disease with substantial and growing socio‐economic burden. In this multifactorial disease, aging, environmental, and genetic factors contribute to neurodegeneration and dopamine (DA) deficiency in the brain. Treatments aimed at DA restoration provide symptomatic relief, however, no disease modifying treatments are available, and PD remains incurable to date. Mathematical modeling can help understand such complex multifactorial neurological diseases. We review mathematical modeling efforts in PD with a focus on mechanistic models of pathogenic processes. We consider models of α‐synuclein (Asyn) aggregation, feedbacks among Asyn, DA, and mitochondria and proteolytic systems, as well as pathology propagation through the brain. We hope that critical understanding of existing literature will pave the way to the development of quantitative systems pharmacology models to aid PD drug discovery and development.